Limits and Difficulties in Implementing the Strategic Trade Policy - Liviu-George Maha; Andreea-Nicoleta Donici; Andreea Maha (CES Working Papers, 2012)
This paper provides a critical analysis of the strategic trade policy, in terms of limitations and difficulties involved in its implementation. Even there are many arguments used by its supporters for justifying the importance of this type of measures, it is impossible for the state to formulate useful interventionist policies, given the empirical difficulties involved in modeling markets with imperfect competition. Also, any potential gain created by government intervention can dissipate through the entry of new firms, stimulated by the possibility of such profits, while the need of a general equilibrium increases the difficulty of interventionist process. There are also some risks induced by using strategic trade policy, the risk of retaliation and a trade war with the country affected by the measure and the diversion of government intervention by certain interests, transforming it into an inefficient income redistribution national program.
Keywords: E20; E40; E58; E60; 330; strategic trade policy; free trade; retaliation; trade war; general equilibrium; interest groups Romania